ASME 2008 International Manufacturing Science and Engineering Conference, Volume 2 2008
DOI: 10.1115/msec_icmp2008-72533
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Nanometric Machining Under Realistic Cutting Conditions

Abstract: Molecular Dynamics (MD) simulations of nanometric machining of single-crystal copper were conducted at a conventional cutting speed (5m/s) and different depths of cut (0.724 – 2.172 nm). The simulations were carried out to predict cutting forces and investigate the mechanism of chip formation at the nano level. The effect of tool rake angles and depths of cut on the mechanism of chip formation were also investigated. Tools with different rake angles, namely 0°, 5°, 10°, 15°, 30°, and 45°, were used. It was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…The ratio between the tangential, lateral and the normal components of the cutting forces is similar to that found in conventional machining for the Morse and the EAM potentials. The results of the EAM model are comparable with those in [25,26], where the EAM potential best describes the metallic bonding in the copper atoms. In contrast, the pair potentials (both LJ and Morse potentials), do not incorporate the many-body effects; they have no environmental dependence and they do not account for the directional nature of bonding in metals [29] .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The ratio between the tangential, lateral and the normal components of the cutting forces is similar to that found in conventional machining for the Morse and the EAM potentials. The results of the EAM model are comparable with those in [25,26], where the EAM potential best describes the metallic bonding in the copper atoms. In contrast, the pair potentials (both LJ and Morse potentials), do not incorporate the many-body effects; they have no environmental dependence and they do not account for the directional nature of bonding in metals [29] .…”
Section: Resultssupporting
confidence: 83%
“…They modelled two abrasives that cut through a workpiece of 100 000 atoms over its whole length at 100 m/s. Pei et al [25] and Promyoo et al [26] carried out MD simulations of the nanometric cutting of copper with diamond tool. They both studied the effects of the tool rake angle and the interatomic potentials (Morse and EAM) on the process.…”
Section: Fundamentals Of MD and Examples Of Md Simulations Of Nanomacmentioning
confidence: 99%
“…(Oluwajobi & Chen, 2011a) From Figures 11 -13, it can be observed that the cutting forces variation is lowest for the EAM potential. The results of the EAM model are comparable with those of (Pei et al, 2006, Promyoo et al, 2008, and the EAM potential best describes the metallic bonding in the copper atoms. In contrast, the pair potentials (both LJ and Morse potentials), do not incorporate the many-body effects; they have no environmental dependence and they do not account for the directional nature of bonding in metals (Li et al, 2008).…”
Section: Modelling With Eam Potentialsupporting
confidence: 67%
“…2. Atomistic Interaction in Nanometric Machining (Ikawa et al, 1991, Promyoo et al, 2008 www.intechopen.com Figure 2 shows the time increment (Δt), in which every atom changes its position and interacts with its surrounding neighbour atoms in a manner that is determined from the interatomic potential function.…”
Section: Cutting Forcesmentioning
confidence: 99%
“…Figures 8 and 9 show the variations in cutting and thrust forces per unit width, respectively, at a cutting speed of 5 m/s. The results obtained at a cutting speed of 500 m/s (Promyoo, 2008) and from the study of Komanduri et al (1999) are also given.…”
Section: Cutting Forcesmentioning
confidence: 96%